The effect of temperature on the reproduction of Limnodrilus hoffmeisteri (Oligochaeta: Tubificidae) - Nascimento,Haroldo L. S. (2009)
The tubificid worm Limnodrilus hoffmeisteri Claparede, 1862 is widely used as an indicator of organic pollution in aquatic environments. Nevertheless, little is known about its biology. The present work aimed to compare the reproductive rate of L. hoffmeisteri raised at three different temperatures (15, 20 and 25°C). Seventy-five adult individuals were kept in fifteen 250 ml beakers (five individuals per beaker) containing sand and dechlorinated tap-water each. Beakers were arranged so as to form three groups of five. Each group was kept in a given temperature for 21 days. Results show that worms raised at 25°C produced a significantly larger number of eggs compared to those raised either at 15 or 20°C, as observed in the tropical tubificid Branchiura sowerbyi Beddard, 1892.